Energy balance for the production of grain, meat, and biofuel in specialized and mixed agrosystems - Sá, Jerusa Maia e; Urquiaga, Segundo; Jantalia, Cláudia Pozzi; Soares, Luis Henrique de Barros; Alves, Bruno José Rodrigues; Boddey, Robert Michael; Marchão, Robélio Leandro; Vilela, Lourival (Pesquisa Agropecuaria Brasileira, 2013)
The objective of this work was to evaluate the energetic efficiency of mixed and specialized production systems of grain and meat, and the energy balance in bioenergy production. Agronomic data from 20‑year farming with specialized and mixed agrosystems were used. As specialized agricultural systems, the following ones were evaluated: grass pasture; grass with legume pasture; and continuous grain production under no tillage or conventional plough tillage. As a mixed system, the integrated crop‑livestock was evaluated under no tillage or conventional plough tillage. The agricultural activity were considered energy input, while grain yield and meat production the energy output. The agricultural products obtained in mixed systems showed energy balance and total production of renewable energy equivalent to the those yielded by the specialized systems. The energy balance of soybean biofuel showed positive values both in mixed and in specialized systems regardless of the soil tillage managements. Among the analyzed soybean and maize biofuels, the greatest energy balance was observed in maize bioethanol. The biofuels produced in all production systems show a positive energy balance and can be considered energetically sustainable.